Representações sociais de integrantes do movimento hip-hop em Ponta Grossa: seus elementos e o lazer - Polichuk, Naja Kayanna (2011)
This research aims at identifying what are the social representations of members of the Movement in Hip-Hop Ponta Grossa-PR. The specific objectives are to describe how members experience the Hip-Hop Movement, pointing out which are the activities developed within the Hip-Hop Movement, to identify whether these activities are integral to recreational activities. For the objectives to be achieved construct a theoretical framework guided discussions about the concept of social representation, leisure and about the Hip-Hop Movement. This research is qualitative and methodological procedures was the exploratory research. To collect data we used the techniques of semistructured interviews and participant observation. The method of analysis of the data was the Hermeneutic.